2019
DOI: 10.1021/jacs.9b05932
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroxymethylation of Alcohols Enabled by Cerium Photocatalysis

Abstract: Dehydroxymethylation, the direct conversion of alcohol feedstocks as alkyl synthons containing one less carbon atom, is an unconventional and underexplored strategy to exploit the ubiquity and robustness of alcohol materials. Under mild and redox-neutral reaction conditions, utilizing inexpensive cerium catalyst, the photocatalytic dehydroxymethylation platform has been furnished. Enabled by ligand-to-metal charge transfer catalysis, an alcohol functionality has been reliably transferred into nucleophilic radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(93 citation statements)
references
References 74 publications
4
88
0
1
Order By: Relevance
“…77 The Zuo lab later disclosed an application of ceriumcatalyzed b-scission to the dehydroxymethylation of alcohols and functionalization of these nucleophilic alkyl synthons in radical-mediated conjugate additions (Scheme 23). 73 Through a double-excitation mechanism, C-C bond b-cleavage can be exploited to form alkyl radicals with concomitant extrusion of formaldehyde. A catalyst system comprising CeBr 3 with Bu 4 NBr under 365 nm irradiation was found to be integral to the efficiency of the reaction, allowing for excitation of both the in situ formed Ce(IV)-alkoxide species to the LMCT excited state and…”
Section: Transition Metal-mediated Homolysismentioning
confidence: 99%
“…77 The Zuo lab later disclosed an application of ceriumcatalyzed b-scission to the dehydroxymethylation of alcohols and functionalization of these nucleophilic alkyl synthons in radical-mediated conjugate additions (Scheme 23). 73 Through a double-excitation mechanism, C-C bond b-cleavage can be exploited to form alkyl radicals with concomitant extrusion of formaldehyde. A catalyst system comprising CeBr 3 with Bu 4 NBr under 365 nm irradiation was found to be integral to the efficiency of the reaction, allowing for excitation of both the in situ formed Ce(IV)-alkoxide species to the LMCT excited state and…”
Section: Transition Metal-mediated Homolysismentioning
confidence: 99%
“…[24] As ac onsequence,w ef ocused on the silver-mediated dehydroxymethylative fluorination of carbohydrates in aqueous media. Being aware of the fact that the radical deoxymethylation of pyranoid primary alcohols is underexploited, [25] we commenced our studies with glucopyranoside alcohol 1a as the model substrate to optimize the reaction conditions (see the Supporting Information, Table S1). After diligent evaluation of various reaction parameters including the type and amount of silver salt, the amount of Selectfluor,and the nature of the solvent, we found that the reaction proceeded smoothly in the presence of Ag 2 CO 3 (0.5 equiv) and Selectfluor (5-10 equiv) as the oxidant and fluorine source in acetone/H 2 O( v/v 4:1), and provided fluorosugar 2a in the best yield of 86 %w ith a5R/5S ratio of 1.7:1 at room temperature in 3h( Table 1).…”
Section: Substrate Scopementioning
confidence: 99%
“…For example, it is common to take a commercial ketone and yield the targeted alcohol 3g by Wittig olefination and BH 3 reduction (Scheme 3). 46,47 Knoevenagel condensation and O 2 /NaBH 4 functional group interconversion have the potential to be a more practical/operationally simple two-step sequence as it avoids pyrophoric and air-sensitive butyllithium and boranes.…”
Section: Paper Synthesismentioning
confidence: 99%